2006
DOI: 10.2175/193864706783710695
|View full text |Cite
|
Sign up to set email alerts
|

Technical and Economic Evaluation and Selection of Sulfate ION Removal Technologies for Recovery of Water from Mineral Concentrate Transport Slurry

Abstract: This paper presents the findings of a comprehensive evaluation for a Primary Mineral Processing (PMP) company that contracted Battelle to identify economical technology to remove sulfate ion (SO 4 2-) from mineral slurry transport (MST) water, now disposed of as a waste, for reuse or sale. MST water is separated from product by dewatering a sulfidic mineral concentrate slurry prior to loading and shipping of the solid product. The MST water sulfate ion concentration is between 400 and 1720 mg/L, below the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Despite this, other authors have described Al(OH)3 being used as reagent in sulfate removal (e.g. [25] albeit with longer reported reaction times of 30-300 min. [ ] report the use of amorphous Al(OH)3 at a dose of 0.784 g/L which reduced sulfate concentrations from 1043 ppm to 213 ppm in 15 min.…”
Section: Effectiveness Of Aluminum Hydroxide As An Aluminiferous Reagentmentioning
confidence: 99%
“…Despite this, other authors have described Al(OH)3 being used as reagent in sulfate removal (e.g. [25] albeit with longer reported reaction times of 30-300 min. [ ] report the use of amorphous Al(OH)3 at a dose of 0.784 g/L which reduced sulfate concentrations from 1043 ppm to 213 ppm in 15 min.…”
Section: Effectiveness Of Aluminum Hydroxide As An Aluminiferous Reagentmentioning
confidence: 99%
“…Sulfate Precipitation With Chemical Reagents. Bowell (2004) and Usinowicz et al (2005) reviewed all the available technologies to remove sulfate ions from mine water. Both these studies concluded that sulfate removal through precipitation of ettringite can provide one most-efficient treatment solution.…”
Section: Chemical-precipitation Technologiesmentioning
confidence: 99%
“…In the SAVMIN process, aluminum is recovered for recycling from ettringite, whereas the CESR process disposes of the precipitated ettringite as sludge without aluminum recovery. The key precipita-tion reaction occurring in both of these sulfate-removal processes with industrial water is as follows (Usinowicz et al 2005):…”
Section: Chemical-precipitation Technologiesmentioning
confidence: 99%
“…Bowel (2004) and Usinowicz et al (2006) reviewed all the available technologies to remove sulfate ions from mine water. Both these studies concluded that sulfate removal through precipitation of ettringite can provide one most efficient treatment solution.…”
Section: Sulfate Precipitation With Chemical Reagentsmentioning
confidence: 99%
“…In the SAVMIN process, aluminum is recovered for recycle from ettringite whereas CESR process disposes the precipitated ettringite as sludge without aluminum recovery. The key precipitation reaction occurring in both these sulfate removal processes with industrial water is shown below (Usinowicz et al 2006).…”
Section: Sulfate Precipitation With Chemical Reagentsmentioning
confidence: 99%